The sphinx's enigma: the political thought of Samuel Benchimol and Djalma Batista - Silva, Ricardo Lima da; Régis, Alex Sander Pereira; Marinho, Venâncio José Michiles (Laboratório Editorial Faculdade de Ciências e Letras, 2019)
In the fifties and sixties decades of the twentieth century, several intellectuals began to reflect on what would be the most effective ways to integrate the Amazon to Brazil. At that time, the region was emerging of a long period of economic stagnation and became a space of capitalist reproduction during the military dictatorship with the establishment of the development project, Amazon Operation.  The present article intends to analyze and understand the main politicals ideas of Djalma Batista e Samuel Benchimol, who had an active voice in the debates about the paths to be traced by the region. We seek to systematize the reflexions of these authors about the function of State, national/regional integration and development as they are key ideas in their thought. The thought of these authors was generated by the necessity of the regional elites to put an end to the economic stagnation after the First World War; it was also a way to try to solve the regional issue, facing it as a social and political problem that would only be solved with the social and economic integration to Brazil.